The Transdermal Delivery of Therapeutic Cannabinoids - Haleh Mahmoudinoodezh; Srinivasa Reddy Telukutla; Sukhvir Kaur Bhangu; Ava Bachari; Francesca Cavalieri; Nitin Mantri (MDPI AG, 2022)
Recently, several studies have indicated an increased interest in the scientific community regarding the application of Cannabis sativa plants, and their extracts, for medicinal purposes. This plant of enormous medicinal potential has been legalised in an increasing number of countries globally. Due to the recent changes in therapeutic and recreational legislation, cannabis and cannabinoids are now frequently permitted for use in clinical settings. However, with their highly lipophilic features and very low aqueous solubility, cannabinoids are prone to degradation, specifically in solution, as they are light-, temperature-, and auto-oxidation-sensitive. Thus, plant-derived cannabinoids have been developed for oral, nasal-inhalation, intranasal, mucosal (sublingual and buccal), transcutaneous (transdermal), local (topical), and parenteral deliveries. Among these administrations routes, topical and transdermal products usually have a higher bioavailability rate with a prolonged steady-state plasma concentration. Additionally, these administrations have the potential to eliminate the psychotropic impacts of the drug by its diffusion into a nonreactive, dead stratum corneum. This modality avoids oral administration and, thus, the first-pass metabolism, leading to constant cannabinoid plasma levels. This review article investigates the practicality of delivering therapeutic cannabinoids via skin in accordance with existing literature.